Novel graphite-like carbon nitride/organic aluminum diethylhypophosphites nanohybrid: Preparation and enhancement on thermal stability and flame retardancy of polystyrene - Zhu, Yulu; Shi, Yongqian; Huang, Zheng-Qi; Duan, Lijin; Tai, Qilong; Hu, Yuan (Composites. Part A, Applied science and manufacturing, 2017)
Graphite-like carbon nitride (g-C3N4) was innovatively modified by diethylphosphinic acid through hydrogen bonding; g-C3N4/organic aluminum diethylhypophosphites (g-C3N4/DAHPi) hybrid (denoted as CDAHPi) was synthesized by salification reactions, and subsequently incorporated into PS matrix to prepare composites through melt blending method. Thermal data showed that g-C3N4 could protect DAHPi from external heat, leading to improved thermal stability of DAHPi. Moreover, it was found that the introduction of the hybrid reduced the values of heat release rate (HRR) and total heat release (THR) of the composites. Compared with those of pure PS, the HRR and THR of PS/CDAPHi4 decreasing by 43% and 21% respectively were observed at loadings as low as 4.0wt%. The PS/CDAHPi exhibited an additional advantage in suppression of pyrolysis gas production in comparison with neat PS. In addition, the additive showed higher interfacial adhesion with PS.